Analisis Pengaruh Kualitas Auditor, Likuiditas, Profitabilitas, Dan Solvabilitas Terhadap Opini Audit Going Concern Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Ajikusuma, Viki, Dra. Rina Trisnawati, Ak, M.Si, Ph.D (2016)
This research aims to test empirically the influence of auditor quality, liquidity, profitability and solvability to administration Going Concern Audit Opinion. In this research the type of used data is quantitative data with a population of 120 companies listed in the indonesia Stock Exchange in 2012-2015. The analytical method used is logistic regression analysis with the study sample was 30 companies were selected based on purposive sampling method during the four years. From the analysis results can be seen that the quality of auditors, liquidity, and profitability does not affect the going concern audit opinion. Meanwhile effect on the solvability going concern audit opinion.